2019
DOI: 10.1186/s12987-019-0133-x
|View full text |Cite
|
Sign up to set email alerts
|

The need for mathematical modelling of spatial drug distribution within the brain

Abstract: The blood brain barrier (BBB) is the main barrier that separates the blood from the brain. Because of the BBB, the drug concentration-time profile in the brain may be substantially different from that in the blood. Within the brain, the drug is subject to distributional and elimination processes: diffusion, bulk flow of the brain extracellular fluid (ECF), extra-intracellular exchange, bulk flow of the cerebrospinal fluid (CSF), binding and metabolism. Drug effects are driven by the concentration of a drug at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 246 publications
(348 reference statements)
2
60
0
1
Order By: Relevance
“…Next, we study how the drug distribution within the 3D brain unit is affected by v blood , P, T m-in and T m-out . Fig 9 shows cross-sections (for y ¼ 1 2 y r and z = 0) of the 3D brain unit at Table 2.…”
Section: The Effect Of the Brain Capillary Blood Flow Velocity In Thementioning
confidence: 99%
“…Next, we study how the drug distribution within the 3D brain unit is affected by v blood , P, T m-in and T m-out . Fig 9 shows cross-sections (for y ¼ 1 2 y r and z = 0) of the 3D brain unit at Table 2.…”
Section: The Effect Of the Brain Capillary Blood Flow Velocity In Thementioning
confidence: 99%
“…In addition, the distribution of therapeutics entering the brain may be inhomogeneous, raising difficulties in ensuring proper target engagement. Vendel et al [159] reviewed the complexity of modelling brain distribution for therapeutics and concluded that more work is still needed. Another example of complexity of drug delivery to brain is the intranasal route.…”
Section: Drug Deliverymentioning
confidence: 99%
“…In principle, the compartment model combined with a comprehensive understanding of where and when drugs penetrate should allow us to make predictions concerning the order in which drug resistance mutations occur. In practice, understanding where, when, and how certain drugs reach parts of the body is complicated (Vendel et al, 2019). Indeed, different studies have measured different relative penetrances of drugs into the tissue versus the plasma.…”
Section: Issues With Identifying and Measuring Compartmentsmentioning
confidence: 99%